CONCEPTUALIZATION OF “REINTEGRATION” CONCEPT IN CONDITIONS OF MILITARY CONFLICT IN UKRAINE - Kolenichenko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article analyzes the scientific research of scientists who studied the problem of reintegration of veterans, and it has been found that there is a discussion in the scientific literature about the content of the term "reintegration". It has been emphasized that the increase in the number of veterans leads to the emergence of problems that lie in the field of social work as a science and are related to the reintegration of veterans into society after returning from the combat zone. It has been proven that scientists consider the main problems related to reintegration through the prism of conflicts that arise in the process of communication of a veteran with his immediate environment; that important factors that determine the process of reintegration of veterans are the immediate social environment of veterans and the readiness of the community to accept veterans, creating conditions for their successful reintegration; the important role of the community in the process of reintegration of veterans and focused attention on the unpreparedness of most communities for the return of veterans and the lack of any support for veterans from the community. The goal of the article is to conceptualize approaches to the concept of “reintegration” and identify the features of reintegration of veterans in the conditions of the military conflict in Ukraine. Achieving the set goal is possible through the use of theoretical research methods: analysis and generalization of domestic and foreign scientific literature on the definition of the concept of “reintegration” with elements of induction and deduction to characterize the state of research development and conceptualization of the concept of “reintegration”; analysis and synthesis in order to determine the initial provisions of the article. The generalization of the views of scientists regarding the content of the concept of “reintegration” gave us grounds for identifying the features of the reintegration of veterans in the conditions of the military conflict in Ukraine.